Inhibition of non canonical HIV-1 tat secretion through the cellular Na+,K+-ATPase blocks HIV-1 infection - Agostini, Silvia; Lusic, Marina (EBioMedicine, 2017)
Besides its essential role in the activation of HIV-1 gene expression, the viral Tat protein has the unusual property of trafficking in and out of cells. In contrast to Tat internalization, the mechanism involved in extracellular Tat release has so far remained elusive. Here we show that Tat secretion occurs through a Golgi-independent pathway requiring binding of Tat with three short, non-consecutive intracytoplasmic loops at the C-terminus of the cellular Na+,K+-ATPase pump alpha subunit. Ouabain, a pump inhibitor, blocked this interaction and prevented Tat secretion; virions produced in the presence of this drug were less infectious, consistent the capacity of virion-associated Tat to increase HIV-1 infectivity. Treatment of CD4+ T-cells with short peptides corresponding to the Tat-binding regions of the pump alpha subunit impaired extracellular Tat release and blocked HIV-1 replication. Thus, non canonical, extracellular Tat secretion is essential for viral infectivity.